2013
DOI: 10.1073/pnas.1216499110
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic characterization and crystal structure of a small molecule inactivator bound to plasminogen activator inhibitor-1

Abstract: Plasminogen activator inhibitor type-1 (PAI-1) is a member of the serine protease inhibitor (serpin) family. Excessive PAI-1 activity is associated with human disease, making it an attractive pharmaceutical target. However, like other serpins, PAI-1 has a labile structure, making it a difficult target for the development of small molecule inhibitors, and to date, there are no US Food and Drug Administration-approved small molecule inactivators of any serpins. Here we describe the mechanistic and structural cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 58 publications
1
35
0
Order By: Relevance
“…Based on this study, in 2013, the same group [93] published the crystallographic structure of PAI-1 with the related polyphenolic compound CDE-096 (49) (Fig. 15), a novel synthetic molecule.…”
Section: Polyphenolic Derivativesmentioning
confidence: 98%
“…Based on this study, in 2013, the same group [93] published the crystallographic structure of PAI-1 with the related polyphenolic compound CDE-096 (49) (Fig. 15), a novel synthetic molecule.…”
Section: Polyphenolic Derivativesmentioning
confidence: 98%
“…These efforts, however, have been limited by a lack of crystal structure information on vitronectin-bound PAI-1 (47). Polyphenolic inhibitors of PAI-1 (CDE-066 and 096) synthesized on the basis of the structure of small molecules identified by a high throughput screen were found to bind to the sB/sC pocket of PAI-1 with an IC 50 of 32 μM and 25 nM, respectively (Figure 1) (48,49). CDE-096 induces allosteric conformational changes affecting the flexibility of PAI-1 and preventing it from binding to PA and decreasing vitronectin binding (49).…”
Section: Pharmacological Inhibition Of Pai-1mentioning
confidence: 99%
“…Polyphenolic inhibitors of PAI-1 (CDE-066 and 096) synthesized on the basis of the structure of small molecules identified by a high throughput screen were found to bind to the sB/sC pocket of PAI-1 with an IC 50 of 32 μM and 25 nM, respectively (Figure 1) (48,49). CDE-096 induces allosteric conformational changes affecting the flexibility of PAI-1 and preventing it from binding to PA and decreasing vitronectin binding (49). CDE-096 was still able to interact with vitronectin-bound PAI-1, although the magnitude of polarization was decreased 7.3-fold compared to binding free PAI-1.…”
Section: Pharmacological Inhibition Of Pai-1mentioning
confidence: 99%
“…This correspondence suggests that our simulations have identified residues that play important roles in mediating the latency transition. We note that Li et al (34) recently identified a pocket at the interface of sheets B and C that appears to be important for PAI-1 function, and a number of this subset of energetically important residues (K176, F207, E226, G264, and T267) are clustered in this region.…”
Section: Significant Interactions During the Conformational Reactionmentioning
confidence: 99%